(untitled) (Global Journal of Medical Research, 2016)
The only host for H. pylori is human and it is found to be present in stomach, duodenum, oesophagus and rectum. H. pylorus is responsible for causing chronic infections and therefore its complete eradication from the society is very much essential. This article therefore aims to review the recent treatment options prevalent for the eradication of this dreadful disease.